The Influence of Financial Management Education, Financial Literacy, and Personal Financial Attitudes on Paylater Usage: Hedonistic Lifestyle as a Mediator - Rasya Ninda Fajarrohmah; Ifah Rofiqoh (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the influence of Financial Management Education, Financial Literacy, and Personal Financial Attitudes on Paylater usage, with Hedonic Lifestyle as a mediating variable. It aims to determine whether these financial factors significantly impact Paylater use and whether Hedonic Lifestyle mediates the relationship. The research was conducted using a survey method with purposive sampling, targeting 600 university students across Indonesia who have used or are currently using Paylater services. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The findings show that Financial Management Education, Financial Literacy, and Personal Financial Attitudes significantly influence Paylater usage. However, Hedonic Lifestyle does not have a significant direct effect and does not mediate the relationship between financial knowledge, attitudes, and Paylater use. This suggests that financially literate individuals with responsible financial attitudes may still choose to use Paylater not due to hedonistic motivations, but because of practical reasons such as convenience, urgency, or ease of access. The novelty of this study lies in its integrated model that combines financial behavioral factors with lifestyle aspects an approach that is still rarely explored in Paylater-related research.